2012
DOI: 10.1515/joc-2012-0047
|View full text |Cite
|
Sign up to set email alerts
|

Phase Noise Influence in Long-range Coherent Optical OFDM Systems with Delay Detection, IFFT Multiplexing and FFT Demodulation

Abstract: We present a study of the influence of dispersion induced phase noise for CO-OFDM systems using FFT multiplexing/IFFT demultiplexing techniques (software based). The software based system provides a method for a rigorous evaluation of the phase noise variance caused by Common Phase Error (CPE) and Inter-Carrier Interference (ICI) including -for the first time to our knowledge -in explicit form the effect of equalization enhanced phase noise (EEPN). This, in turns, leads to an analytic BER specification. Numeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Recently, the interaction between the electronic dispersion equalization and the laser phase noise, which leads to an effect of equalization enhanced phase noise (EEPN), has attracted the research interests due to its significant impacts in long-haul optical transmission systems [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. W. Shieh et al have reported the theoretical assessment of the EEPN from the enhanced LO phase noise, and they also investigated the EEPN induced time jitter in coherent transmission systems [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the interaction between the electronic dispersion equalization and the laser phase noise, which leads to an effect of equalization enhanced phase noise (EEPN), has attracted the research interests due to its significant impacts in long-haul optical transmission systems [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. W. Shieh et al have reported the theoretical assessment of the EEPN from the enhanced LO phase noise, and they also investigated the EEPN induced time jitter in coherent transmission systems [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Long-haul high-capacity optical fibre networks can be seriously deteriorated by physical impairments in the transmission systems, e.g. chromatic dispersion (CD), polarization mode dispersion, laser phase noise (PN) and fibre nonlinearities [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Since the compensation and mitigation of these system impairments can be implemented in electrical domain, the combination of coherent optical detection, advanced modulation formats and digital signal processing (DSP) has become one of the most popular and promising solution for new-generation long-haul and metro optical communication networks to perform close to the limit of Shannon capacity, based on the knowledge of signal amplitude and phase [21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, since the coherent demodulation is linear and all information of the received signals can be detected, signal processing approaches i.e. tight spectral filtering, CD equalization, PMD compensation, laser PN estimation, and fiber nonlinearity compensation can be implemented in electrical domain [33][34][35][36][37][38][39][40]. The typical block diagram of the coherent optical transmission system is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%